Emotional Interaction and Artificial Intelligence in Educational Research - Mayrene, Flores Hinostroza Elizeth; Basantes, Amparo Cazorla; Martínez, Magda Francisca Cejas; Salas, Francisco Paul Pérez; Jose, Mendoza Velazco Derling (Journal of Ecohumanism, 2024)
The use of artificial intelligence in higher education has inspired this research, which aims to develop a theoretical ap-proach to emotional interaction within the educational sphere. This study was conducted using a qualitative approach, rooted in the interpretative-humanistic paradigm. At the National University of Chimborazo in Ecuador, the research was carried out with a population of 310 students from the psychopedagogy program, selecting a homogeneous sample of twenty-eight ninth-semester students. Data collection tools included participatory observation guides and semi-structured interviews. The data obtained were analyzed using Atlas.Ti software, which enabled the triangulation of emotional inter-actions during the educational process and an exploration of how artificial intelligence can facilitate the understanding of these dynamics. Through this analysis, four main constructs were identified: cognitive influences of AI, emotional inter-action and artificial intelligence in educational research, social-affective bonds in educational research and AI, and AI as a facilitator of relationships. This approach underscores the importance of integrating the emotional dimension in education, suggesting that artificial intelligence can enhance not only academic learning but also enrich interpersonal relationships and emotional management within the educational environment. Thus, it aims to contribute to more meaningful learning that meets the emotional needs of students.